AC susceptibility study in Bi1.6Pb0.4Sr2(Ca1−xNdx)2Cu3Oδ ceramic superconductors - Malik, A.I.; Çelebi, S.; Halim, S.A. (Elsevier BV, 2002)
We have studied the frequency dependence of the AC susceptibility in polycrystalline samples of Bi1.6Pb0.4Sr2(Ca1−xNdx)2Cu3Oδ. AC susceptibility measurements in the range 20–1000 Hz show that as the frequency increases, the intra and intergranular AC loss peaks move to higher temperature, and also the height and the width of the peaks increase. When we plot the peak height as a function of the AC field amplitudes, we observe a valley-like behavior. We qualitatively discuss experimental results in the framework of the critical state model, estimate the effective volume fraction of the grains and determine the temperature dependence of the intergranular critical current density by means of the best fit of the calculated data for the experimental matrix susceptibility. Since the granularity effect was very pronounced at low field range, we separated the contribution of the grains and matrix from the total measured AC susceptibility.